IMPLEMENTATION OF THE PRINCIPLE OF SECURITY IN THE PROCESS OF ELECTRONIC FIRST TIME LAND REGISTRATION TO REALIZE LEGAL CERTAINTY FOR THE COMMUNITY - Prasetyo, Windu Gandung; Kurniati, Nia; Rubiati, Betty (Jurnal Poros Hukum Padjadjaran, 2024)
In the current industrial era 4.0, the development of information technology has influenced all aspects of people's lives, including implementing government duties. One area that is also affected by advances in information technology is the land sector. The enactment of ATR/BPN Ministerial Regulation No.1 of 2021 and PP No. 18 of 2021 is a concrete manifestation of the use of developments in information technology in the land sector. Implementing land registration through an electronic system is expected to benefit the community, especially in terms of guaranteeing legal certainty. However, in its implementation, it turns out that various problems are still found, one of which is the neglect of the principles in land registration, namely the principle of security. The principle of security requires that land registration be carried out carefully and meticulously to guarantee legal certainty for holders of land rights. In this research, we will examine the application of the principle of security in electronic land registration to ensure legal certainty for the community. Using the normative juridical approach and analytical descriptive method, it can be said that the implementation of the principle of security in land registration via an electronic system that has been carried out by the Land Office has not been optimal. This can be seen from the many disputes and cases in the land sector that are still occurring and of course they are detrimental to society.